Parallel Struggles of Religious Moderation Activists Amid Hindu-Muslim Tensions in India and Political Polarization in Indonesia - Parinduri, M. Azmi Alkhosyi Parinduri (GoResearch - Research & Publishing House, 2025)
The phenomenon of religious and political polarization has created serious pressure on religious moderation work, both in India and Indonesia. In India, interfaith activists who strive to maintain harmony between Hindu and Muslim communities often face stigmatization, labeling themselves as